The nexus between social inequality and CO2 emissions revisited: Challenging its empirical validity. Issue 89 (November 2018) - Mader, Sebastian
Highlights: Rigorous inquiry of the inequality –CO2 emissions nexus suggests a flat relation. The results invalidate the positive relation found by Knight et al. (2017) and Jorgenson et al. (2017). Thus, cap-and-dividend schemes are not suitable for an effective climate policy. Moreover, in the U.S. rising energy prices substantially reduce CO2 emissions. Wealth levels drive consumption-based but not production-based CO2 emissions. Abstract: Recently, a discussion about the ambiguity of the nexus between social inequality and anthropogenic CO2 emissions has emerged. Macroeconomic panel studies applying region and time fixed effects (FE) regression models and measuring inequality by the Gini coefficient discovered a flat relationship. Only two of these studies substituting Gini by the more appropriate share held by the top 10 percent of the income or wealth distribution find a positive effect. This paper revisits this nexus and challenges the empirical validity of the contribution of an increase in wealth and income inequality to higher CO2 emissions lately found by Knight et al. (2017) on country-level and by Jorgenson et al. (2017) on U.S. state-level. The positive inequality effects spotted in these two studies are not robust with respect to the regions and time spans observed as well as to the inequality indicators, estimation techniques, and confounders selected. Hence, this in-depth investigation suggests that there is no sound empirical evidence for a substantial nexus between social inequality and CO2 emissions. After all, lately proposed policy approaches combining efficient cap-and trade programs with income and wealth redistribution (so-called cap-and-dividend schemes) are not, by themselves, suitable for an effective climate policy. In fact, the analysis points at the relevance of treating key predictors of CO2 emissions including energy prices for the U.S. for effective climate change mitigation.